2018
DOI: 10.1021/acssuschemeng.8b04421
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Polycarbonates from a Citric Acid-Based Rigid Diol and Recycled BPA-PC: From Synthesis to Properties

Abstract: Here we present a series of homopolycarbonates (homo-PCs) and copolycarbonates (co-PCs) based on a novel bicyclic diol octahydro-2,5-pentalenediol (OPD) from naturally occurring citric acid and bis­(hydroxyethyl ether) of bisphenol A (BHEEB), synthesized by melt polycondensation. The recently developed OPD has been shown to be a highly rigid and thermally stable building block suitable for the construction of performance polymers. BHEEB, which was obtained from the chemical recycling of BPA-PC, was used to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…The signals at around δ 4.5, δ 4.33, and δ 3.96 ppm can be assigned to the protons, numbered as 3, 7, and 10, on carbons that were linked to hydroxyl groups in isomer A′ and A, respectively, while the protons (numbered as 1 and 5) on bridged carbons exhibited overlapped multiplets at around 2.39 and 2.21 ppm, respectively . The integral area ratio of proton peaks 3 to 7, 3 to 10, and 1 to 5 are 6.1:1, 5.6:1, and 3.2:1, respectively, implying that the molar ratio of A to A′ is around 3:1 . In the FTIR spectra of OPD, an identical strong absorption band at 3295 cm –1 can be observed, corresponding to the typical −OH stretching vibration on the bicycles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The signals at around δ 4.5, δ 4.33, and δ 3.96 ppm can be assigned to the protons, numbered as 3, 7, and 10, on carbons that were linked to hydroxyl groups in isomer A′ and A, respectively, while the protons (numbered as 1 and 5) on bridged carbons exhibited overlapped multiplets at around 2.39 and 2.21 ppm, respectively . The integral area ratio of proton peaks 3 to 7, 3 to 10, and 1 to 5 are 6.1:1, 5.6:1, and 3.2:1, respectively, implying that the molar ratio of A to A′ is around 3:1 . In the FTIR spectra of OPD, an identical strong absorption band at 3295 cm –1 can be observed, corresponding to the typical −OH stretching vibration on the bicycles.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, octahydro-2,5-pentalenediol (OPD) was synthesized from dimethyl-1,3-acetonedicarboxylate (derived from naturally occurring citric acid) and glyoxal through Weiss–Cook condensation, decarboxylation under acidic conditions and reduction with NaBH 4 . OPD, with two fused cyclopentane rings, exhibits excellent rigidity and thermal stability, which envisioned to greatly restrict the motion of the polymer chain if incorporated in the macromolecular structures, leading to the high performance of polymers (high T g and tensile strength). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, PEOB and PTOB synthesized from diacid in this work had higher T g values than the room temperature; thus, they were brittle. This phenomenon can be ascribed to the low density of the entangled strand caused by the rather rigid OBDA moiety predisposing the glassy polyester to form a weak crack upon stretching. , With the increasing number of methylene group sequences in the diol moiety, the mobility of the polyester chain segments was enhanced, and a “brittle-to-ductile” transition occurred for PBOB, with a moderate tensile toughness (ε m ∼ 85%) (Figure S7). In addition, high-molecular-weight PBOB displayed a satisfactory tensile strength (σ b ) of 12 MPa, comparable to that of low-density polyethylene (LDPE), due to the rigid OBDA units.…”
Section: Resultsmentioning
confidence: 99%
“…Aliphatic bio-based polyesters possess advantages such as desirable biodegradability, reduced toxicity, and general biocompatibility. However, poor thermal stability and mechanical strength are common defects in these polyesters, especially for amorphous aliphatic polyesters. ,, The incorporation of aromatic building blocks is an appealing strategy to address this limitation, ,, FDCA has emerged as a new alternative bio-based aromatic diacid to petroleum-derived terephthalic acid and has been selected by the U.S. Department of Energy as one of the top 12 value-added biomass-derived chemicals. The FDCA-based polyesters poly (ethylene 2,5-furandicarboxylate) (PEF), poly­(propylene 2,5-furandicarboxylate) (PPF), and poly­(butylene 2,5-furandicarboxylate) (PBF) are regarded as the green polyesters with the most potential value, having high thermal stability, tensile strength, and gas barrier properties .…”
Section: Resultsmentioning
confidence: 99%
“…Gao, et al have recently reported on octahydro-2,5-pentalenediol (OPD, Scheme 1), derived from citric acid. 19,20 Just like isosorbide, it has a rigid V-shaped structure, but instead of furan rings it has two cisfused carbocycles. This alicyclic diol yielded PCs with good thermal stability (thermal decomposition at 276°C) and T g s up to 80°C, demonstrating that the mimicking of the isosorbide bicyclic structure is an efficient approach to increase the chain rigidity of polymers.…”
Section: Introductionmentioning
confidence: 99%